Treatments and outcomes for patients with myelodysplastic syndrome (MDS) by Revised International Prognostic Scoring System (IPSS-R) scores at the Huntsman Cancer Institute (HCI) - Willis, Connor; Tan, Malinda Sunnita; Bauer, Hillevi; Au, Trang H.; Tantravahi, Srinivas Kiran; Gilreath, Jeffrey; Kovacsovics, Tibor; Cao, Xiting; Sadek, Islam; Stenehjem, David D. (Journal of clinical oncology, 2021)
e19034Background: IPSS-R is used to classify risk of disease progression and guide treatment decisions for patients with MDS. Recent data shows mutational profiling may improve the prognostic stratification of MDS. Minimal real-world evidence exists for this population. Methods: A retrospective cohort study assessed real-world, patient-level data from adults diagnosed with MDS between 2010-2019 at HCI. All data were obtained from electronic medical records via chart review. IPSS-R scores were manually calculated from lab and cytogenetic data within 30 days of diagnosis. Patients with an intermediate to very-high IPSS-R score comprised the higher risk (HR) cohort. Primary objectives were to assess treatment patterns & clinical outcomes in the HR cohort. Results: Of the 259 MDS patients at HCI, 90 had an available IPSS-R score at diagnosis (ANC results were missing for 64% of cohort). After excluding clinical trial participants, 65 patients were included. Distribution of IPSS-R scores was: 15% very low (n = 10), 28% low (n = 18), 22% intermediate (n = 14), 23% high (n = 15), & 12% very high (n = 8). The average age of HR subjects was 67 years. 57% of HR patients were female (n = 21), 92% were white (n = 34), 8% (n = 3) had autoimmune disorders, & 8% (n = 3) had cerebrovascular disease. 14% (n = 5) of NGS-tested HR patients had TP53 alterations, while the most frequently altered gene was DNMT3A at 17% (n = 6). In the HR cohort, HMA was used to treat 62% of patients (n = 23) (median 2 cycles), while 27% (n = 10) received no MDS-related medication, and 11% (n = 4) received other MDS-related medications (lenalidomide, ruxolitinib, hydroxyurea). Second-line treatment was received by 9% of HR patients (n = 3). 35% of HR patients (n = 13) underwent stem-cell transplantation. Complete or partial response was achieved by 21% of HR patients treated with a HMA (n = 5); the remaining patients had stable disease (39%, n = 9), disease progression (26%, n = 6), or died (4%, n = 1). Transfusion independence was achieved by 60% of HMA-treated HR patients (n = 3) (median duration = 151 days from treatment initiation). Disease progression or death occurred in 89% of HR patients (n = 33) during the study period with a median progression free survival (PFS) of 8.3 months. PFS was significantly shorter for HR patients with TP53 alterations compared to wild-type (HR: 5.75, 95% CI (1.34-24.64)), using cox regression. Median overall survival for HR patients was 18.8 months. Conclusions: These results show HR patients have a low likelihood of achieving & maintaining complete remission. In addition, limited treatment options for HR patients further reveals a large unmet need. Specific genetic profiles may indicate the need for more aggressive treatments and management of relevant comorbidities. Updated results will be presented, including LR patients & economic outcomes.